Life-course Factors and Later Life Health in Eastern and Western Europe - Sakkeus Luule; Schwanitz Katrin; Abuladze Liili; Rudissaar Uku (Bundesinstitut für Bevölkerungsforschung, 2026)
Human development and ageing are lifelong processes, where earlier life conditions and events are interlinked with later life outcomes. Patterns of inequality within and among cohorts emerge over time as products of the interplay between institutional arrangements and individual life, often dependent on childhood or earlier life circumstances. The life conditions and experiences of older adults in Eastern and Western Europe differ signifi cantly, but whether their cumulative effects on later life outcomes vary across these two regions has not been compared. We explore the effects of socioeconomic position, the experience of a period of hunger, the dispossession of assets, and discrimination suffered by parents in respondents’ life courses on later life health inequalities in Europe. Self-reported health, everyday activity limitations, and cognitive functioning are the main outcomes that provide an adequate overview of different health domains. We mainly use data from the seventh wave of the Survey of Health, Ageing, and Retirement in Europe (SHARE 2017) and restrict our sample to respondents aged 65 and older from 26 European countries (N=41,566). We fi nd that older people in Eastern Europe fare worse in self-rated health and everyday activity limitations than Western Europeans, while Eastern Europeans indicate somewhat better outcomes in cognitive functioning. A disadvantaged socioeconomic position in childhood and adulthood has the strongest association with all health outcomes, followed by the experience of hunger over the life course for the whole of Europe. However, we do not fi nd diverging associations between life-course factors and health outcomes in Eastern and Western Europe. We argue that self-reported health, everyday activity limitations and cognitive functioning have to be analysed within their own frameworks and cannot yield conclusions that are uniform for all health outcomes. Moreover, major generalisations either about Eastern or Western Europe must be treated with caution as the regions have very different historical as well as demographic developments and thus cannot be treated as uniform.